To compare the efficiencies of shock waves extracorporeal lithotripsies (ESWL) versus ureterorenoscopy (URS) to remove proximate ureteric stones - Muhammad Adnan Sarwar; Farhan Khan; Naveed Soomro; Iftikhar Ahmed; Muhammad Mashkoor Aslam; Ahsan Ali Arain; Hafiz Bilal Murtaza (Journal of University Medical & Dental College, 2023)
Introduction: - Urolithiasis is a widespread health problem. The objective of this research was to contrast the use of shock waves extracorporeals lithotripsies’ (ESWL) versus ureterorenoscopy (URS) for the proximal ureteric stones treatment. Ureteric stone is a common disease of urinary system in Pakistan. Despite ongoing success in endourological stone treatment, question about optimal management of proximal ureteric stone still remains debatable amongst urologist; therefore this study is being performed to find an appropriate and effective tool to treat ureteric stones.Objective: - For patients with large proximal ureteric gallstones, our goal was to compare the advantages of ureterorenoscopy with shock wave extracorporeal lithotripsy (ESWL) (10–15 mm).Settings: The Karachi-based Sindh Hospital of Urology & Transplantation's Urology Department.Duration: 6 months from 28-01-2022 to 28-07-2022Design: Randomized control trialSubject and Methods: Sixty people were enrolled in the trial, all of whom had a single, radio-opaque stone in the proximal ureter detected by IVU. Thirty patients received ESWL and thirty received URS, both at random. After 3 weeks, x-ray KUB was used to monitor patients in both groups. A computerized pre-structured proforma was used for all data collection.Result: - The victims were 27.58 6.20 years old on aggregate.There were 38(63.3%) male and 22(36.7%) female. Efficacy of URS treatment was significantly high as compare to ESWL [93.33% vs. 60%; p 0.002]. Conclusion: - This research shows that the results support the hypothesis that URS is more effective for proximal ureteric stone clearance than ESWL.